CANVAS BUSINESS STRATEGY IN THE APPLICATION OF LOCAL CREDITS IN BANK BCA - Tirtayasa, Yohan (Dinasti Publisher, 2020)
In meeting the needs of additional funds, BCA has taken into account the needs of customers; provided in the form of credit facilities. The business model of this local credit facility has been well thought out so as to make this facility in demand among customers. Analysis uses 9 business model segments ranging from determining customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. These 9 segments will be interrelated to support BCA as a whole and in line with the vision, mission, values, needs and other activities of BCA.